2016
DOI: 10.1016/j.intimp.2016.02.023
|View full text |Cite
|
Sign up to set email alerts
|

Emodin attenuates TNF-α-induced apoptosis and autophagy in mouse C2C12 myoblasts though the phosphorylation of Akt

Abstract: Emodin, a major component of Rheum palmatum, has been reported to significantly protect neural tissue against apoptosis and autophagy. However, the effects and underlying mechanisms of action of emodin in muscle atrophy are still poorly defined. In this study, we investigated the protective effects and the underlying mechanisms by which emodin acts on tumor necrosis factor alpha (TNF-α)-induced apoptosis and autophagy in mouse C2C12 myoblasts. Emodin, at various concentrations, decreased TNF-α-induced apoptosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(12 citation statements)
references
References 62 publications
1
11
0
Order By: Relevance
“…But, the phenomenon was evidently abated by EMO disposition. The results were partly similar to Chen et al uncovered that EMO lightened TNF-a-induced apoptosis and autophagy in mouse C2C12 myoblasts [28]. These observations indicated that EMO weakened hypoxia-triggered PC-12 cell injury.…”
Section: Discussionsupporting
confidence: 88%
“…But, the phenomenon was evidently abated by EMO disposition. The results were partly similar to Chen et al uncovered that EMO lightened TNF-a-induced apoptosis and autophagy in mouse C2C12 myoblasts [28]. These observations indicated that EMO weakened hypoxia-triggered PC-12 cell injury.…”
Section: Discussionsupporting
confidence: 88%
“…Thus, the protective effect of emodin against CLP-induced intestinal barrier injury can be partially explained by the increased expression of TJ proteins. In recent years, numerous scientific reports described that emodin has an anti-inflammatory effect and can reduce the expression of the inflammatory factor TNF-α (55)(56)(57). Compared with expression in the corresponding CLP group, the protein expression levels of claudin-3 in the CLP + emodin group showed a continuous and uniform distribution, with a smoother edge and an enhanced positive signal.…”
Section: Discussionmentioning
confidence: 91%
“…This is based on studies where reduced autophagosome formation and maturation were observed with TNFα blockers 145,153 . It is a chain of events where TNFα-associated upregulation of autophagy (by inducing ROS production) is mediated by activating the Jun kinase pathway and inhibiting the Akt pathway 145,157 . Similarly, in vitro experiments conducted in fibrotic kidney and hepatoma cells have confirmed that another inflammatory cytokine, TGFβ, also upregulates autophagic genes such as Beclin 1, Atg5, and Atg7 145,158 .…”
Section: Association Of Autophagy and Inflammatory Phenotype In Metsmentioning
confidence: 99%